2019
DOI: 10.1093/femspd/ftz035
|View full text |Cite
|
Sign up to set email alerts
|

Genetic association between mannose-binding lectin polymorphisms and viral hepatitis: a meta-analysis

Abstract: Some previous genetic association studies have tried to investigate potential associations between mannose-binding lectin (MBL) polymorphisms and viral hepatitis. However, the results of those studies were not consistent. Therefore, we performed the current meta-analysis to explore associations between MBL polymorphisms and viral hepatitis in a large pooled population. A systematic literature research of PubMed, Web of Science, Embase and CNKI was performed to identify eligible studies for pooled analyses. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The results of studies on the potential association between MBL polymorphisms and CHB have been inconsistent. A meta-analysis showed that polymorphisms in the MBL promoter and exon 1 are significantly associated with HBV infection, and Allele D is associated with HBV persistence ( Qie et al., 2019 ). Ficolin-2 levels are positively correlated with the degree of liver inflammation in patients with CHB.…”
Section: Innate Immunity Cells In Patients With Chronic Hepatitis Bmentioning
confidence: 99%
“…The results of studies on the potential association between MBL polymorphisms and CHB have been inconsistent. A meta-analysis showed that polymorphisms in the MBL promoter and exon 1 are significantly associated with HBV infection, and Allele D is associated with HBV persistence ( Qie et al., 2019 ). Ficolin-2 levels are positively correlated with the degree of liver inflammation in patients with CHB.…”
Section: Innate Immunity Cells In Patients With Chronic Hepatitis Bmentioning
confidence: 99%